What is going on with fatigue of additively manufactured metals?. Issue 5 (17th June 2019) - Solberg, Klas; Berto, Filippo
Abstract: This brief communication gives an overview of fatigue behaviour and assessment of additively manufactured metals. The high cycle fatigue behaviour of as‐built and post‐processed additively manufactured superalloy 718, stainless steel (316L and 17‐4PH), and Ti‐6Al‐4 V is compared with their wrought counterparts. Further, different approaches used for assessment of the fatigue behaviour are presented.